Nahwu Learning Development Innovation in Formal Diniah Education PP Al-Mubarok Manggisan Wonosobo - Azizah, Latifah Nur; Nahda , Aida Wafiq; Azzah, Alifa Noor; Kholiq, Davit Muhammad; Huda, Khoirul (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
Formal Diniyah Education at the Al-Mubarok Manggisan Islamic boarding school has innovations in developing nahwu learning. The objectives of this research are to determine innovations in the development of nahwu learning and the factors that influence the successful implementation of nahwu learning innovations in Formal Diniyah education at the Al-Mubarok Manggisan Islamic boarding school. From the above objectives, this research uses descriptive qualitative research with a case study method carried out by interviews and observations. Formal Diniyah Education at the Al-Mubarok Manggisan Islamic boarding school was successful in developing nahwu learning innovations using the amtsilati method.